Before rana plaza: towards a history of labour organizing in Bangladesh’s garment industry - Siddiqi, Dina Mahnaz (© 2016 Taylor and Francis., 2018)
This book chapter was published in the book name Labour in the Clothing Industry in the Asia Pacific [© 2017 by Taylor and Francis] and the definitive version is available at: http://doi.org/10.4324/9781315647326 The book's website is at https://www.taylorfrancis.com/books/e/9781317297673